Real process improvement using the CMMI - West, Michael (Auerbach Publications, 2004)
"Real Process Improvement Using the CMMI®" provides real-world concepts and techniques for CMMI-based process improvement that are as effective as they are innovative. Professionals at all levels - from systems engineers to CEOs - will find a wealth of practical guidance and new ways to look at model-based process improvement, resulting in benefits for large and small organizations in many environments. Using plain language and enlightening illustrations, the author identifies the most critical concepts of the CMMI, and details how to turn these concepts into real process improvement
Includes bibliographical references (pages 261-264), and index. - Print version record
Keywords: Capability maturity model (Computer software); Production management; Quality control; Quality Control; Modèle de maturité de la capacité (Génie logiciel); Production; Gestion; Qualité; Contrôle; quality control; TECHNOLOGY & ENGINEERING; Industrial Technology; TECHNOLOGY & ENGINEERING; Industrial Engineering; BUSINESS & ECONOMICS; Production & Operations Management; Administração da produção; Controle da qualidade; Instructional and educational works; Matériel d'éducation et de formation